Role of Interventional Radiology in Management of C-Section Scar Ectopics - Rajvanshi, Utsav; Garg, Puneet; Sindhwani, Geetika; Singh, Resham (Acta medica Lituanica, 2026)
Background: Cesarean Scar Ectopic Pregnancy (CSEP) is an uncommon but potentially fatal syndrome defined by the implantation of the gestational sac inside the scar tissue of a prior cesarean surgery. The incidence of cesarean deliveries is rising, currently accounting for up to 6% of all ectopic pregnancies. CSEP causes unique challenges in diagnosis and treatment because it can lead to serious problems like uterine rupture, placenta accreta spectrum, bleeding, and infertility. Case report: This report describes two patients with Type I CSEP who were treated by using a less invasive method that involved injecting methotrexate and potassium chloride (KCl) guided by ultrasound. Both patients showed improvement, quickly lost fetal heart activity, and had lower blood beta hCG levels without any issues during the procedure. Transvaginal ultrasonography was important in diagnosis and therapy planning. Interventional radiology approaches, especially image-guided targeted therapy, provide promising fertility-preserving options compared to the traditional surgery. The research backs this careful approach for patients who are stable, with Uterine Artery Embolization (UAE) being helpful in some cases. Conclusion: Our study highlights the importance of using a team of specialists and shows that interventional radiology is a key part of improving treatment for CSEP, making it safer for patients, lowering risks of complications, and protecting their ability to have children in the future.